Infection and Inflammation: Potential Triggers of Sudden Infant Deaths - Amanda Cox (Frontiers Research Topics, 2016)
There is a growing body of evidence that infectious agents or their products contribute to events leading to unexpected infant deaths. This issue summarizes the current information on the interactions between genetic background of the infant, environmental and developmental risk factors, and the microbial flora of the infant that could trigger lethal responses to common infections.